The Influence of Busy Book Media on the Ability to Recognize Number Concepts in 5-6 Year Old Children at TK Islamiyah Pontianak Tenggara: The Influence of Busy Book Media on the Ability to Recognize Number Concepts in 5-6 Year Old Children at TK Islamiyah Pontianak Tenggara - Meri Sri Sugita; Halida; Annisa Amalia (Universitas Nahdlatul Ulama Surabaya, 2024)
This study was conducted to determine: The Influence of Busy Book Media on Number Concept Recognition Ability in 5-6 Year Old Children at TK Islamiyah Pontianak Tenggara. The technique used in this research was a quantitative approach with an experimental research method, specifically using a pre-experimental design known as one group pretest-posttest. The subjects of the study were all children in group B at TK Islamiyah Pontianak Tenggara, totaling 12 children. Sample selection was done using Purposive Sampling technique from the entire population, ensuring that the chosen sample met the predefined criteria to aid the research process. Data collection techniques included test, observation, and documentation processes. Descriptive data analysis was used to determine mean, median, mode, and standard deviation. Prerequisite tests conducted were normality test and hypothesis testing. The pretest results (before using the busy book) had an average score of 5.53, while the posttest results (after using the busy book) showed an average score of 9.20. Based on the significant level of 5% (2.106), the paired sample t-test analysis resulted in a calculated t-value (6.862) that was greater than the critical t-value (2.160), with a significance (2-tailed) of 0.000 < 0.05. This indicates that the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. Therefore, it can be concluded that there is an influence of using busy book media on the ability to recognize number concepts at TK Islamiyah Pontianak Tenggara.